Limit theorems for the maximum of sums of independent random processes - Matsak, I. K.; Plichko, A. M.; Sheludenko, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We study the conditions for the weak convergence of the maximum of sums of independent random processes in the spaces$C[0, 1]$ and $L_p$ and present examples of applications to the analysis of statistics of the type $ω 2 $.